2019
DOI: 10.4314/jae.v23i4.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Value Addition on Farm Income of Sweet Potato Farmers in Kwara State, Nigeria

Abstract: The study examined the effect of value addition on farm income of sweet potato-based farmers in Kwara State, Nigeria. A three-stage sampling procedure was employed to select 145 respondents. Structured questionnaire coupled with interview schedule were used to collect primary data. Multiple regression was used to analyse the effect of different value addition activities on income received from sweet potatoes. Also, marginal effects were obtained to analyse the effect of each independent variable separately on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
2
1
0
Order By: Relevance
“…As can be seen in table 3, the net farm income of married farmers is 91k more than that of the farmers that were not married. This affirmed the assertion ofAlalade et al, (2019) that the farming households…”
supporting
confidence: 74%
See 1 more Smart Citation
“…As can be seen in table 3, the net farm income of married farmers is 91k more than that of the farmers that were not married. This affirmed the assertion ofAlalade et al, (2019) that the farming households…”
supporting
confidence: 74%
“…As can be seen in table 3, the net farm income of married farmers is 91k more than that of the farmers that were not married. This affirmed the assertion of Alalade et al, (2019) that the farming households have a perception that the addition of one working member in a family enhances farm operations thereby increasing farm production and ultimately increasing household income, and reducing cost of hired labour. Farming experience has a positive effect on the net farm income of the farmers.…”
Section: Costs and Returns Of Sweet Potato Production In The Study Areasupporting
confidence: 60%
“…A recent survey of sweetpotato producers, marketers and processors in Nigeria (Kano and Kwara States) and Ghana (Bawku) revealed that much of the sweetpotato crop was sold into urban centres (between 40 and 90% depending on gender of producer and area), and between 58% (in Kano) and 75% (in Kwara) was consumed as fried product (Ssali et al ., 2021). However, household surveys in sweetpotato‐producing local government areas (LGAs) in Kwara State, Osun and Ogun States in Nigeria showed a heavy reliance on dry chips for flour production, which contributed to household food security and avoided postharvest spoilage of perishable roots (Omoare et al ., 2015; Adeyonu et al ., 2016; Alalade et al ., 2019). Less emphasis was given to frying at the household level since most of the sweetpotato frying was done off‐farm.…”
Section: Utilisation and Demand For Sweetpotato In West Africamentioning
confidence: 99%
“…According to Clark (2019), sweet potatoes can be processed to create a variety of snack and dessert foods, as well as sweet potato juices, drinks, soups, baby food, and ice cream. According to Alalade (2019), a range of items, including flour, crisps, canned sweet potatoes, starch, and sweet potato beer, can be made from sweet potatoes, including sparri (sweet potato garri).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the possibility of them participating in the value addition of sweet potatoes is greatly determined by their access to credit, level of training, and quantity of sweet potatoes collected. In a related study, Alalade (2019) found that farmers in Kwara State performed tasks like sorting and packaging, cutting and drying in the sun, grinding the sweet potatoes into flour, baking, adding flavorings, manufacturing juice and jam, and flour preparation. Additionally, the size of the household, total amount produced, availability of finance, farm size, proximity to the market, and membership in a group all have an impact on their involvement in sweet potato value addition.…”
Section: Introductionmentioning
confidence: 99%